Illustrated Thesaurus - Beal, George; Nang Chan Yeema (New York, USA Larousse Kingfisher Chambers Inc., 1994)
Has been specially created to help children find just the word they need to make what they write and say more precise and imaginative with thousands of guidewords and an enormous choice of synonyms and antonyms.
Keywords: Juvenile Nonfiction